Preliminary evidence of Regional Interdependent Inhibition, using a 'Diaphragm Release' to specifically induce an immediate hypoalgesic effect in the cervical spine. Issue 2 (April 2017) - McCoss, Calum A.; Johnston, Ross; Edwards, Darren J.; Millward, Charles
Summary: In clinical practice, Osteopaths and Manual Therapists commonly direct treatment towards the diaphragm by the use of a 'Diaphragm Release'. Currently, there is paucity within the literature to support the use of this technique, specifically in pain outcomes. This research aims to support a neurophysiological mechanism based upon the osteopathic principle "The body is a unit". Demonstrating that directing treatment to distal tissue which is neurologically related can reduce pain in the originating spinal segments. This study investigated the immediate hypoalgesic effects of a 'Diaphragm Release' on pain pressure thresholds in the cervical spine. A single-blind, randomised, sham-controlled, repeated measures within subject, crossover design was conducted on 17 asymptomatic subjects. Pain pressure thresholds were measured bilaterally in the C4 paraspinal musculature, lateral end of the clavicle and upper third of the tibialis anterior before and after a 'Diaphragm Release'. Results demonstrated a statistically significant hypoalgesic effect was only found in the spinal segment C4 in both the right (p = 0.016) and left (p = 0.004) sides. Averaging the hypoalgesic effect from both sides equates to a 17.17% change which is considered clinically significant, the effect magnitude was calculated to be small but educationally significant for the right ( d = 0.26) and left ( d = 0.40) sides. This study supports a novel neurophysiological mechanism, Regional Interdependent Inhibition, to induce a hypoalgesic state at segmentally related spinal segments, specifically C4. Suggesting that directing treatment towards the diaphragm, using a 'Diaphragm Release', could induce an immediate clinically and statistically significant hypoalgesic effect local to the fourth cervical segment due to its relationship with the phrenic nerve.